2005
DOI: 10.1002/ar.a.20230
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A storage in hepatic stellate cells in the regenerating rat liver: With special reference to zonal heterogeneity

Abstract: Under physiological conditions, hepatic stellate cells (HSCs) within liver lobules store about 80% of the total body vitamin A in lipid droplets in their cytoplasm, and these cells show zonal heterogeneity in terms of vitamin A-storing capacity. Vitamin A is essential for the growth and differentiation of cells, and it is well known that liver cells including HSCs show a remarkable growth capacity after partial hepatectomy (PHx). However, the status of vitamin A storage in HSCs in the liver regeneration is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 30 publications
1
21
0
1
Order By: Relevance
“…Serum aminotransferases are the most useful measures of liver cell injury [53]. In our study, high AF-ALB was significantly associated with high ALT and high total protein and marginally associated with high AST.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Serum aminotransferases are the most useful measures of liver cell injury [53]. In our study, high AF-ALB was significantly associated with high ALT and high total protein and marginally associated with high AST.…”
Section: Discussionsupporting
confidence: 54%
“…Liver hepatocytes govern the uptake, transfer, metabolism, and homeostasis of vitamin A. It was previously reported [53, 71] that serum concentrations of vitamin A were lower in individuals with chronic liver diseases and were related to the severity of the condition. Hepatic stellate cells that mediate liver fibrosis are usually affected as a result of liver injury and could lead to vitamin A deficiency [72].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that HSCs are activated 3–5 days after 70% hepatectomy (21, 22), and parameters of HSC activation are returned to control level at 14 days after operation. We did not observe increases in hepatic collagen α1(I) expression 10 days after removing the left lobectomy because the reaction of HSCs to left lobectomy might have been recovered at this time point.…”
Section: Discussionmentioning
confidence: 99%
“…Liver regeneration induced by partial hepatectomy (PH) is associated with the loss of HSC-associated vitamin A content (13) and up-regulation of the HSC activation markers such as ␣-smooth muscle actin (␣SMA), IL-6, and hepatocyte growth factor (14), suggesting that HSCs undergo activation and support a regenerative response. Regulation of HSC myofibroblastic activation by the neurotrophin receptor p75NTR is actually crucial for supporting liver regeneration (10).…”
mentioning
confidence: 99%